2008 38th Annual Frontiers in Education Conference 2008
DOI: 10.1109/fie.2008.4720645
|View full text |Cite
|
Sign up to set email alerts
|

Microfabrication of a resistance temperature detector by freshman engineering students

Abstract: A hands-on microfabrication project was developed and implemented for Louisiana Tech's integrated freshman engineering curriculum. The project involved the design and fabrication of a simple nickel resistance temperature detector. The project is part of a series of hands-on projects being developed for the freshman engineering curriculum as part of a "Living with the Lab" concept that utilizes a microcontroller-based robotics kit to increase experiential learning. The project was initially piloted in two secti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 8 publications
(8 reference statements)
0
9
0
Order By: Relevance
“…ENGR 121 students complete the fish tank project that involves controlling the temperature and salinity of a small volume of water, as shown in Figure 3. Students build almost the entire system from scratch, including the pump (from ENGR 120), the conductivity sensor, and a microfabricated resistance temperature detector (RTD) 13 . This project provides an outstanding opportunity for students to learn the fundamentals of salt water chemistry, conservation of mass, and conservation of energy on a just-in-time basis as they implement their projects.…”
Section: The First Year Engineering Curriculum: "Living With the Lab"mentioning
confidence: 99%
See 1 more Smart Citation
“…ENGR 121 students complete the fish tank project that involves controlling the temperature and salinity of a small volume of water, as shown in Figure 3. Students build almost the entire system from scratch, including the pump (from ENGR 120), the conductivity sensor, and a microfabricated resistance temperature detector (RTD) 13 . This project provides an outstanding opportunity for students to learn the fundamentals of salt water chemistry, conservation of mass, and conservation of energy on a just-in-time basis as they implement their projects.…”
Section: The First Year Engineering Curriculum: "Living With the Lab"mentioning
confidence: 99%
“…Additional anecdotal evidence suggests that students are developing lifelong learning skills. In focus group meetings conducted in Spring 2008 13 , students reported that "I like that they (the instructors) didn't always tell us what to do -we had to figure it out on our own." However, "there was always someone there to help -faculty and classmates.…”
Section: ≠ While Taking Engr 120 How Much Instruction Did You Receivmentioning
confidence: 99%
“…The Living with the Lab curriculum uses design and fabrication projects involving DC electrical circuits, computer programming, solid modeling, machining, rapid-prototyping, working with hand tools, testing, data analysis and plotting 5,[11][12][13] . Students assemble their own set of hand tools.…”
Section: Introductionmentioning
confidence: 99%
“…The leadership is somewhat familiar with gender issues as they relate to undergraduate education, faculty retention and success. The college has been successful with a number of relevant programs, employing for approximately a dozen years an integrated model for the first two years of undergraduate Page 22.390.2 engineering education [4], [5], [6], [7], [8], and [9]. These efforts have reaped significant rewards in student success, retention, and satisfaction.…”
Section: Introductionmentioning
confidence: 99%